Effectiveness of an antioxidant preparation with N-acetyl cysteine, alpha lipoic acid and bromelain in the treatment of endometriosis-associated pelvic pain: LEAP study. (September 2018) - Lete, Iñaki; Mendoza, Nicolás; de la Viuda, Esther; Carmona, Francisco
Abstract: Objective: To assess the impact of an antioxidant preparation with N -acetyl cysteine, alpha lipoic acid and bromelain on endometriosis-associated pelvic pain. Study design: Multicenter, open-label, non-comparative clinical trial in a representative sample of women with endometriosis-associated pelvic pain. Results: In total, 398 patients with a mean age of 34.6 ± 7.2 years were treated with a combination of N -acetyl cysteine, alpha lipoic acid and bromelain for 6 months. At baseline, 92.7% of the patients had pain intensity > 4 on the visual analogue scale (VAS); at 3 months of treatment, this percentage decreased to 87.2% (p = 0.074) and at 6 months the percentage was 82.7% (p < 0.05). Conclusions: Women with endometriosis who wish to become pregnant and are treated with a preparation containing N -acetyl cysteine, alpha lipoic acid and bromelain experienced a significant improvement in endometriosis-associated pelvic pain and required lower intake of rescue analgesics.